Le spectre du temps - Lamontagne, Valérie (Ciel variable)

(untitled) (Les Productions Ciel variable, 2005)
Abstract The author considers David Claerbout's work in relation to the overlapping histories of cinema and photography and suggests that the etymological and perceptive frictions that have developed between these media form the crux of the artistry of is installations. Indeed it is this dialogic relationship between photographic and cinematic language, with their past and present temporal logics, and different material qualities, that are seen at play in these video installation works.